Investigating Literal and Figurative Meaning in Song Lyrics: A Semantic Analysis of ‘Fix You’ by Coldplay - Nadya Y.P.Parhusip; Bernieke Anggita Ristia Damanik (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study investigates how literal and figurative meanings are constructed in the song lyrics of “Fix You” by Coldplay through a non-empirical qualitative semantic analysis. The research examines the interaction between denotative and connotative language in shaping emotional representation within musical discourse. Data were drawn from the official lyrics and analyzed using semantic frameworks informed by theories of Lyons, Kreidler, Lakoff, and Johnson. The findings reveal that figurative meanings, particularly metaphors and symbolic expressions, dominate the lyrical structure, while literal expressions function as contextual anchors that support interpretative coherence. Emotional experiences such as loss, hope, and psychological struggle are predominantly conveyed through conceptual metaphors grounded in embodied cognition. The study also highlights that literal and figurative meanings operate in an integrated semantic system rather than as separate interpretative layers. It is concluded that semantic complexity in song lyrics enhances emotional depth and interpretative flexibility, contributing to both linguistic theory and pedagogical applications in language learning contexts.